2020
DOI: 10.1007/s13202-020-00963-9
|View full text |Cite
|
Sign up to set email alerts
|

Rheological impact and economic implications of partial to total substitution of imported bentonite clay for oil and gas drilling operations in Nigeria

Abstract: In less than a decade, there have been two global meltdowns of crude oil price and the latest was caused by the spread of coronavirus disease (COVID-19) in 2020. This is expected to have a negative impact on the global economy, especially on those countries that depend more on the revenue from sales of crude oil. One of the measures that can be taken to survive this kind of situation in the future is to reduce the unit technical cost for producing a barrel of oil by using locally available materials. This rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The thermochemical treatment of Pindinga clay improved the viscosity of the mud (sample P3,3) comparably with that of finished bentonite clay (26 cP) [34]. Hence, Pindinga raw clay can also be used for drilling operations after being treated thermochemically.…”
Section: Shear Stress To Shear Rate Relationshipmentioning
confidence: 94%
“…The thermochemical treatment of Pindinga clay improved the viscosity of the mud (sample P3,3) comparably with that of finished bentonite clay (26 cP) [34]. Hence, Pindinga raw clay can also be used for drilling operations after being treated thermochemically.…”
Section: Shear Stress To Shear Rate Relationshipmentioning
confidence: 94%
“…Studies on beneficiating our local bentonite to see if they can compare with the imported bentonite have been suggested by researchers [10, 12,]. Among the recent studies on beneficiation of Nigeriabentonites using local materials are [17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded from their result that the rheological properties of Ishiagu local clay can be improve and be a good substitute for the foreign imported bentonite when beneficiated with soda ash, potassium chloride and Pac R at their right concentration. Greatest percentage of bentonite used within Nigeria are imported due to the deficiency of the local clays in rheological and fluid loss properties [17] but studies has shown that imported bentonite-local clay blend in the right proportion could save Nigeria 12 to 36% of the cost of bentonite clay used to drill wells in the country [18].…”
Section: Literature Reviewmentioning
confidence: 99%